2002
DOI: 10.1063/1.1432474
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on cation distribution of particle size, lattice parameter, and magnetic properties in nanosize Mn–Zn ferrite

Abstract: In Mn1−xZnxFe2O4 (x=0 to 1) nanosize particles prepared through hydrothermal precipitation we observe a decrease in particle size from 13 to 4 nm with increasing Zn concentration from 0 to 1. The lattice constant, a, for all Mn/Zn concentrations is found to be less than that for the corresponding bulk values. At specific compositions within x=0.35 and 0.5, the temperature dependence of the magnetization exhibits a cusp-like behavior below the temperature at which the nanoparticles undergo a ferri- to para-magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(108 citation statements)
references
References 20 publications
13
93
0
2
Order By: Relevance
“…The patterns clearly show the formation of spinel structure for all samples and indicated that these materials have a well-defined single crystalline phase. By analyzing the XRD patterns it was observed that the peaks (220), (311), (222), (400), (511) and (440) comply with the reported value (Khan et al 2013, Rath et al 2002 and no traces of raw materials are found, thereby confirming that the chemical reaction is completed. lattice parameters were determined.…”
Section: Resultssupporting
confidence: 58%
“…The patterns clearly show the formation of spinel structure for all samples and indicated that these materials have a well-defined single crystalline phase. By analyzing the XRD patterns it was observed that the peaks (220), (311), (222), (400), (511) and (440) comply with the reported value (Khan et al 2013, Rath et al 2002 and no traces of raw materials are found, thereby confirming that the chemical reaction is completed. lattice parameters were determined.…”
Section: Resultssupporting
confidence: 58%
“…However, as in the case of the combustion method, unstable powders, forming hard agglomerates, can be obtained [23]. Because of their unstable character, foreign nonmagnetic phases (e.g., hematite: Fe 2 O 3 ) may occur as a result of the further thermal treatment [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The value of Tc is found to be higher in the case of the ultrafine powder than that in bulk ferrites. This is due to the deviation of cation distribution in a nano-sized particle as in comparison with its bulk counterparts as reported [17]. Licensed Under Creative Commons Attribution CC BY a marginally higher value of Curie temperature than that of the ferrite samples prepared by oxide method.…”
Section: Methodsmentioning
confidence: 75%